THU0110 Effectiveness of Biologic and Nonbiologic Antirheumatic Drugs on Anemia in Adult Patients (PTS) with Rheumatoid Arthritis (RA): New Evidence from Real-World Data. (15th July 2016) - Paul, S.K.; Klein, K.; Best, J.H.; Gale, S.; Pethö-Schramm, A.; Sarsour, K.
Abstract : Background: Anemia, a common complication of RA, has a negative impact on RA symptoms and QOL and is associated with a more severe form of RA. Roles of biologic DMARDs (BDMARDs), including the IL-6 pathway–inhibiting biologic tocilizumab (TCZ), in the pathophysiology of anemia have not been well explored at the population level. Objectives: Evaluate the impact of treatment (Tx) with nonbiologic (NB) and BDMARDs on hemoglobin (Hb) and hematocrit (Hct) in a real-world setting. Methods: Using the GE EMR database, a longitudinal cohort study was conducted on 153, 672 adult RA pts in the US who had ≥6-mo follow-up. 4 mutually exclusive DMARDTx groups (TxGs) were identified: TCZ, tofacitinib (TOFA), other BDMARDs (OBDMARD), and other NBDMARDs (ONBDMARD). To evaluate changes in Hb and Hct at 6 and 12 mo from index date (ID) in different TxGs, unadjusted and adjusted mean (95% CI) changes were obtained, adjusting for age, sex, smoking status, RA duration, concomitant medications, CRP, and other covariates. Separate analyses were conducted for pts with Hb <12/13.5 g/dL for women/men (anemic). Results: Demographics of the cohort were: 55 y mean age, 76% female, 59% white, 57% current or ex-smokers, 44% obese (mean BMI 30 kg/m 2 ). 2% of pts had ischemic heart disease, 2% renal disease, and 7% diabetes. Mean Hb and Hct levels at ID across TxGs were 13.3 g/dL and 40%. Average CRP (1.6 mg/dL) and ESR (23 mm/h) were clinically similar across TxGs at ID. Adjusting for covariates, increases in Hb and Hct levels at 6 and 12 mo were significantly higher in the TCZ group vs the other TxGs (Table). Among anemic pts at ID, increases in Hb and Hct at 6 mo were significantly higher in the TCZ group vs the other TxGs. Significantly greater reductions in ESR and CRP levels over all follow-up periods were observed in the TCZ group vs the other TxGs. Conclusions: This study suggests significant increases in Hb and Hct levels after TCZ therapy vs other nonbiologic and biologic therapies in RA pts with anemia, in line with the potential role of IL-6 in RA pts with anemia. Further study is needed to better evaluate the role of IL-6–based OBDMARDs as a Tx option for RA pts with anemia. Disclosure of Interest: S. Paul Grant/research support from: Genentech, AstraZeneca, Novo Nordisk, Consultant for: GI Dynamics, Speakers bureau: AstraZeneca, GI Dynamics, Novo Nordisk, K. Klein Grant/research support from: Genentech, AstraZeneca, Novo Nordisk, Consultant for: GI Dynamics, J. Best Shareholder of: Roche, Employee of: Genentech, S. Gale Shareholder of: Roche, Employee of: Roche, A. Pethö-Schramm Employee of: F. Hoffmann-La Roche, K. Sarsour Shareholder of: Roche, Employee of: Roche